Las convulsiones y la epilepcia (2000)
¿Qué es la epilepsia?/Causas de epilepsia/Métodos de diagnostico/Tratamiento/Consideraciones psicosociales/Nuevas terapias/Recomendaciones en caso de presentarse una convulsión.